(3MQR GdCeGfi hhLg GdJgGfjs - (3GdbGSe Hf ajQg Hf Nda Hf CMeO GdQYjfj, CHh eMeO GdTGWHj,J (B590 (3g` s
(3ChdgG (B:s
(3bGd GdTjN CHh GdbGSe Hf ajQI GdQYja Ke GdTGWHi (B: (3HOCJ HHSe Gddg ai GdfXe ChdkG JHGQc QMeGfkG QMjeG hehFdG s
(3BNQgG (B:s
(3hJHOi Ydi CUMGHg faMGJgG HZjQJfG RQfHkG hbQfadkG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B180 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B110s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI LGeYI Gdedc YHO GdYRjR GdeQcRjI HLOIs
Keywords: (3GdbQGAGJ hGdJLhjOs